Like day and night: Comparing squad level communications and shooting performance under differing battle drill conditions. (September 2022) - Teo, Grace; Sikorski, Eric; Schreck, Jacquelyn; Goodwin, Gregory
An indicator of squad lethality is the ability to execute battle drills proficiently in a range of real-world situations and environments. While it is a common understanding that military night operations are vastly different from day operations, there is limited research comparing how squad communications and shooting performance differ from day to night in the field. Communication and shooting data were collected from 18 squads that executed a battle drill in the day, and again at night. In the night drills, there were illumination aids of muzzle flashes, chemlights, and Soldier worn night vision devices. The present field study focused on the support-by-fire team, whose central role was to generate suppressive fire which requires substantial teamwork. Findings revealed day-night differences in Soldier communications, firing activity, and the roles of various weapons in generating suppressive fire. Implications for day and night training are also discussed.